Expenditure elasticities of demand for major food items in south-east Nigeria - Nweke, F.I.; Okorji, E.C.; Njoku, J.E.; King, D.J. (1994)
Expenditure elasticities were estimated for yam and cassava and for seven other food items widely consumed by the people of south-east Nigeria. For all households, the combined elasticity estimate for yam was above unity and almost as high as that of meat. For high expenditure households, however, it was significantly below unity but still positive. The estimate for any cassava product was below unity but positive for all households combined. For high expenditure households, especially urban households, the estimate for all cassava products combined was negative, but that for gari, a high-quality processed cassava product, although still below unity, was positive and higher than tlie estimate for yam. The estimates suggest that market potentials exist for increased production of root and tuber crops in the area. The estimates also suggest that although in certain forms of preparation cassava may be an inferior food item, in other forms, it is far from being inferior; it may even be superior to yam. This suggests that there is need for improvement in cassava-processing technology to improve quality and expand the market for that root crop.